High-resolution terrestrial climate, bioclimate and vegetation for the last 120,000 years - Beyer, Robert M.; Krapp, Mario; Manica, Andrea (Scientific data, 2020)
The variability of climate has profoundly impacted a wide range of macroecological processes in the Late Quaternary. Our understanding of these has greatly benefited from palaeoclimate simulations, however, high-quality reconstructions of ecologically relevant climatic variables have thus far been limited to a few selected time periods. Here, we present a 0.5° resolution bias-corrected dataset of global monthly temperature, precipitation, cloud cover, relative humidity and wind speed, 17 bioclimatic variables, annual net primary productivity, leaf area index and biomes, covering the last 120,000 years at a temporal resolution of 1,000–2,000 years. We combined medium-resolution HadCM3 climate simulations of the last 120,000 years with high-resolution HadAM3H simulations of the last 21,000 years, and modern-era instrumental data. This allows for the temporal variability of small-scale features whilst ensuring consistency with observed climate. Our data make it possible to perform continuous-time analyses at a high spatial resolution for a wide range of climatic and ecological applications - such as habitat and species distribution modelling, dispersal and extinction processes, biogeography and bioanthropology. Measurement(s) temperature • precipitation process • vegetation layer • atmospheric wind speed • cloud • humidity Technology Type(s) computational modeling technique Factor Type(s) geographic location • temporal interval Sample Characteristic - Environment climate system Sample Characteristic - Location Earth (planet) Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.12436484